Five Feet Apart by Rachel Lippincott as a Young Adult Literature Genre: Young Adult Literature, Five Feet Apart, characteristics - Danu Wahyono (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2021)
This analysis about Rachel Lippincot’s novel entitled Five Feet Apart. The study focuses on what characteristics of the Young Adult Literature genre in the novel. The objective of the study aims to describe the characteristics of the Young Adult Literature genre found in the novel. The characteristics of Young Adult Literature relate to intrinsic elements of the novel which consist of character, theme, plot, and point of view. The approach used in analysing the novel is the structuralism approach. This research uses the descriptive qualitative method. The result of the analysis states that novel Five Feet Apart fulfils the qualifications of the characteristics of Young Adult Literature. The character of the novel have a physical appearance, the way they behave, and interact with each other. Such as Stella as the main character she have a characteristic of long eyelashes, sandy brown wavy hair, full lia ps, and thin body. While Will Newman as the second of the main character have a physical appearance that is a thin and tall body, deep blue eyes, and dark brown hair. Moreover, the characters in the novel have a change in attitude and way of thinking. As seen from the analysis, the plot in the novel have a faster and the storyline going in the present. Themes in the novel consist of some of themes that is Young Adult Literature and romance because the novel tells about the love story of the two people young adult suffering from lungs illness, that is Stella and Will. There are 2 point of view from the young adult protagonist person as the main character in the novel, in the first chapter begins with Stella point of view and the next chapter continuous by the point of view of Will Newman.